Estudo do comportamento fotoluminescente e morfológico do BaWO4 - Lima, Márcia Valéria Silva (2010)
Several synthesis methods reported in the literature have been developed to the formation of barium tungstate (BaWO4) powders, among these techniques; the microwave-assisted hydrothermal (MH) systems have offered important advantages in the coast reduction and/or formation of crystalline powders. The interest in the tungstates is because of its blue or green luminescence emissions at room temperature, which are able to favor the development of new electro-optic devices. The morphologies and particle sizes of these materials have been controlled by the use of surfactants and/or polymeric agents into the reaction medium. Therefore, the present work reports on the synthesis and MH processing of BaWO4 powders in the presence of ethylene glycol and polyvinylpyrrolidone at different concentrations. Thus, it was verified the influence of these surfactants in the morphology and growth process of the particles as well as its optical properties. The BaWO4 powders were synthesized by the co-precipitation method and processed in MH system at 140 °C for 30 min. These powders were characterized by X-ray diffraction (XRD), Fourier transform Raman (FT-Raman) and Fourier transform infrared (FT-IR) spectroscopies, ultraviolet-visible (UV-vis) absorption spectroscopy photoluminescence (PL) measurements and field-emission gun scanning electron microscopy (FEG-SEM). XRD results indicated that all materials have a scheelitetype tetragonal structure. The characteristic symmetric and anti-symmetric stretching modes of (WO4) groups were detected by the FT-Raman and FT-IR spectroscopies. FEG-SEM micrographs revealed the existence of micro-octahedra with different sizes and well-agglomerated. The optical band gap results suggested the presence of distinct types of structural defects, probably due to the synthesis or MH processing conditions. It was observed PL emissions in the blue and green region of the visible electromagnetic spectrum for the BaWO4 powders when excited with 350 nm wavelength.